Desain Materi Ajar Comprehension Orale A1 Berbasis Analisis Kebutuhan Pembelajar Mengacu pada CECRL untuk Siswa SMA - Gulo, Merlin Soviana; Tambunan, Bony Charlos; Safriza, Nazua; Kholijah, Nita; Soraya, Tengku Ratna; Sibuea, Hadijah Handayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to design A1-level compréhension orale teaching materials based on learner needs analysis referring to the Common European Framework of Reference for Languages (CECRL) for senior high school students. This research employed a descriptive qualitative approach using needs analysis of a lesson plan (RPP) on les endroits publics as the primary data source. Data were collected through documentation study and analyzed using content analysis focusing on oral input, vocabulary, and listening activities. The findings reveal that students need simple and contextual oral input supported by visual media. In addition, they require basic vocabulary related to public places, the ability to understand general meaning and specific information, and continuous listening practice. Based on these findings, the teaching materials were designed into three stages: pré-écoute, pendant l’écoute, and post-écoute, integrating audio and visual media. The designed materials are aligned with the characteristics of A1-level learners in CECRL and are expected to effectively improve students’ listening comprehension skills.